Food for Thought: Leptin and Hippocampal Synaptic Function - Harvey, Jenni (Frontiers in Pharmacology, 2022)
It is well documented that the endocrine hormone, leptin controls energy homeostasis by providing key signals to specific hypothalamic nuclei. However, our knowledge of leptin’s central actions has advanced considerably over the last twenty years, with the hippocampus now established as an important brain target for this hormone. Leptin receptors are highly localised to hippocampal synapses, and increasing evidence reveals that activation of synaptically located leptin receptors markedly impacts cognitive processes, and specifically hippocampal-dependent learning and memory. Here, we review the recent actions of leptin at hippocampal synapses and explore the consequences for brain health and disease.